Song of the poison dragon - West, Tracey, 1965-; Jones, Damien (New York : Branches/Scholastic Inc., 2016)
Petra, the newest dragon master, is scared to death of the Hydra dragon she is supposed to bond with--but when the Hydra accidentally poisons the King, and then her fellow dragon master, Drake, she must find a way to connect with her dragon, because only the Hydra's song can cure them.
440
Accelerated Reader AR
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Fear -- Juvenile fiction; Poisons -- Juvenile fiction; Singing -- Juvenile fiction; Fantasy fiction